Improved Performance of DPFC Using Sliding Mode Controller Method - D Narasimha Rao; T Surnedra; S Tara Kalyani (Institute of Advanced Engineering and Science, 2016)
Modern power systems demand the need of active power flow with the help of Power Electronics control devices is needed. In the family of Flexible AC Transmission devices (FACTS), Dynamic PFC (DPFC) offers the same controlling function as Unified PFC (UPFC), comprising the control of transmission angle, bus voltage and line impedance. A technical modification of UPFC is DPFC in which fluctuations of voltage at DC link is eliminated that enables the individual operation as series and parallel controllers. The concept of DFACTS is used in design of the series converter. The replacement of the high rating three phase series converter with the multiple low rating single phase converters results in cost reduction and increases reliability greatly. This DC Link is used to transfer the real power between two converters in UPFC such as in DPFC which eliminates the 3rd harmonic frequencies at transmission lines. D-FACTS converters are acting as insulation between high voltage phases acts as 1-ᴓ floating with respect to ground. These results in lower cost for the DPFC system compared to the UPFC. This paper describes the comparison of PI and Sliding Mode Controllers which conclude that SMC is a better control strategy compared to PI.